ChemInform Abstract: Ruthenium Catalyzed Hydroboration of Terminal Alkynes to Z‐Vinylboronates. Issue 10 (7th March 2013) - Gunanathan, Chidambaram; Hoelscher, Markus; Pan, Fangfang; Leitner, Walter
Abstract The unprecedented direct, chemo‐, regio‐ and stereoselective preparation of Z‐vinylboronates is achieved using a non‐classical ruthenium hydride pincer complex.